2014
DOI: 10.1097/iae.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

Ranibizumab in the Management of Advanced Coats Disease Stages 3b and 4

Abstract: To the best of the authors' knowledge, this is the largest reported series of late-stage Coats undergoing anti-vascular endothelial growth factor therapy, a homogenous cohort of patients treated with a single agent and with the longest follow-up. This study supports the role of ranibizumab in advanced disease by transient restoration of the hemato-retinal barrier and suppression of neovascularization to facilitate classic treatment. At the last follow-up, the authors report unprecedented anatomical success and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 20 publications
0
26
0
5
Order By: Relevance
“…18,19,20 It has been shown that VEGF levels are elevated in the aqueous humour in Coats’ disease and increase significantly as the disease progresses. 21 Histopathologic examinations have revealed macrophages in the subretinal space and increased vascular permeability caused by these cells, in addition to increased expression of VEGF, which leads to angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19,20 It has been shown that VEGF levels are elevated in the aqueous humour in Coats’ disease and increase significantly as the disease progresses. 21 Histopathologic examinations have revealed macrophages in the subretinal space and increased vascular permeability caused by these cells, in addition to increased expression of VEGF, which leads to angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Even in patients with stage 3B and 4 disease, adjuvant or neoadjuvant application of intravitreal ranibizumab may lead to partial visual recovery. 20 However, there remains the fact that combination therapy with intravitreal anti-VEGF injection may result in vitreoretinal fibrosis and tractional retinal detachment. 23 Laser photocoagulation and cryotherapy were also the most common treatment modalities in the current case series, especially in earlier stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that monthly injections could rapidly stabilize the symptoms [911]. Therefore, we utilized the anti-VEGF intravitreal injection as the initial treatment, then maintained a monthly follow-up period, and finally decided a reinjection according to the disease progress in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the safety and efficacy data for ranibizumab in Coats’ disease is yet lacking, especially for children and the advanced Coats’ disease (stage 3 and over) [9, 10]. Conbercept is a recombinant fusion protein with a high affinity for all VEGF isoforms and has become a common therapy for the treatment of retinal diseases in China.…”
Section: Introductionmentioning
confidence: 99%
“…Experience with ranibizumab is limited in Coats' disease when compared to bevacizumab (Table1). In the largest published case series, Gaillard et al [28] treated 9 patients with severe Coats' disease in stage 3B (5 eyes) and stage 4 (4 eyes) with adjunctive intravitreal ranibizumab in addition to conventional ablative therapy. They observed a progressive retinal reattachment in all cases on an average of 2 months after the injection, which facilitated further treatments, like cryotherapy and laser photocoagulation.…”
Section: E G F I N H I B I T O R S ( B E V a C I Z U M A B Ranibimentioning
confidence: 99%